Pengaruh Brand Ambassador Dan Lifestyle Terhadap Minat Belanja Online Melalui Marketplace Shopee - Putry Ramadhoani; Intisari Haryanti (Journal of Student Research, 2023)
Abstract. This study aims to determine and analyze the influence of brand ambassadors and lifestyle on online shopping interest through the Shopee marketplace. This type of associative research with primary data in and sourced from the research instrument in the form of a Likert-scale questionnaire so that the type of data used is quantitative data. The research population is all consumers who have shopped at Shopee whose number is not known with certainty. The sample of this research was 96 respondents using purposive sampling technique. data collected by observation, questionnaires and literature study. Data analysis techniques using validity test, reliability test, classic assumption test multiple regression, multiple correlation coefficient, t test and f test. The results of the study show that band ambassadors and lifestyle have a significant effect on online shopping interest through the Shopee marketplace.